The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3389/fpubh.2022.913897
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Postoperative Pneumonia: A Case-Control Study

Abstract: BackgroundPostoperative pneumonia is a preventable complication associated with adverse outcomes, that greatly aggravates the medical expenses of patients. The goal of our study is to identify risk factors and outcomes of postoperative pneumonia.MethodsA matched 1:1 case-control study, including adult patients who underwent surgery between January 2020 and June 2020, was conducted in the Second Affiliated Hospital of Kunming Medical University in China. Cases included all patients developing postoperative pneu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…A study found a higher incidence of POP in COPD patients compared to those without this disease 21 . A study by Xiang et al 22 showed a 4.5 times higher incidence of POP in patients with COPD than in unaffected patients. Similarly, the results of our study demonstrated a significantly higher rate of chronic obstructive pulmonary disease in the POP group (p=0.031).…”
Section: Discussionmentioning
confidence: 97%
“…A study found a higher incidence of POP in COPD patients compared to those without this disease 21 . A study by Xiang et al 22 showed a 4.5 times higher incidence of POP in patients with COPD than in unaffected patients. Similarly, the results of our study demonstrated a significantly higher rate of chronic obstructive pulmonary disease in the POP group (p=0.031).…”
Section: Discussionmentioning
confidence: 97%
“…Increased age, chronic obstructive pulmonary disease, emergency surgery, decreased postoperative albumin, prolonged ventilation, and longer duration of bed rest were identified as significant risk factors independently associated with postoperative pneumonia. Postoperative pneumonia is most commonly caused by gramnegative pathogens and multidrug-resistant bacteria accounted for approximately 16.99% of cases [30].…”
Section: Pneumoniamentioning
confidence: 99%
“…investigated the clinical features of patients with HAP after general and digestive surgery and found that esophagectomy accounted for 33% of patients with registred HAP, however in the total number of operated patients, this type of operation represented only 5 % (19). Recently published matched 1:1 case-control study, conducted on adult patients who underwent surgery between January 2020 and June 2020, showed that 2.69% of 1,300 patients after general and digestive surgery acquired HAP (20). Our earlier study showed that 1.4% of all abdominal surgery patients developed HAP in the postoperative period (17).…”
Section: Introductionmentioning
confidence: 99%